Self Affirmation Reduces the Anxiety, LDH and Troponin I in the Clients with Coronary Heart Disease (CHD) - Padoli Padoli; Joko Suwito; Tanto Hariyanto (Universitas Airlangga, 2019)
Introduction: Positive self affirmation is one of the psychological interventions that can be applied to the treatment of coronary heart disease; its effect is currently unknown. The purpose of this study was to prove the effect of self affirmation on anxiety, troponin I and LDH in coronary heart disease patients.Methods: The type and design of the study was quasi-experimental with a non-randomized post-test control group design. Thirty patients with coronary heart disease who were treated in the Camelia room of Dr Soetomo Hospital who had been selected were divided into 2 groups. The first group was given self affirmation twice / day for 20 minutes and the second group had standard care as the control group. After the intervention, anxiety measurements were taken, in addition to the measurement of troponin I and LDH.Results: The results showed that self affirmation reduced anxiety (ρ = 0.03), decreased troponin I (ρ = 0.003) and decreased the lactate dehydrogenase (LDH) levels (ρ = 0.006).Conclusion: Self-affirmation improves the client’s emotions, preventing damage to the heart muscle cells. This is reflected by a decrease in the troponin I and LDH levels which are indicators of heart muscle damage.